Transformational School Leadership in Promoting Project-Based Learning to Enhance Literacy and Numeracy in Elementary Schools - Nur Efendi (The Elementary Journal, 2023)
This study investigates the role of transformational school leadership in promoting project-based learning to enhance literacy and numeracy in an elementary school context. A qualitative case study was conducted at SDN Ngubalan 01 Kalidawir, Tulungagung, Indonesia, involving one principal and six teachers selected purposively. Data were collected through semi-structured interviews, classroom observations, and document analysis, then analyzed using thematic analysis. The findings show that the principal enacted transformational leadership through vision building, mentoring, and continuous instructional support, which encouraged teachers to implement project-based learning. Classroom practices integrated reading, writing, and numerical problem-solving within contextual activities, leading to increased student engagement and participation. Students demonstrated improved reading comprehension, structured writing, and accuracy in basic arithmetic tasks. The alignment between leadership practices and instructional innovation contributed to meaningful learning experiences and strengthened foundational skills. The study concludes that sustained leadership involvement is essential for ensuring the effectiveness of project-based learning in improving literacy and numeracy outcomes in elementary education.